Recrutamento de componentes do banco de sementes do solo em pastagem abandonada na planície de inundação do alto rio Paraná, Brasil. - Chapla, Tatiani Elisa (2009)
In the tropics, large areas originally under forest systems have been converted into pasture. Recovering such environments takes longer than forest recovery following other kinds of disturbance. This study had three goals. First, to find a potential seed bank of woody species able to colonize abandoned pasture in the Upper Paraná River Floodplain. Second, to assess the impact of soil compaction on forest recovery under pasture. Third, to determine the most efficient soil treatment to recruit woody species seedlings from the pasture seed bank. Density and composition of woody species in the soil seed bank were measured using the seedling emergence method. Soil compaction was determined by resistance to penetration. An experiment in the pasture with four treatments was also conducted to assess the recruitment of woody species in the seed bank. The treatments were: the control; mechanical mowing and burning; mechanical mowing and manual weeding with removal of stolons; and mechanical mowing, manual weeding with removal of stolons and soil tillage. A considerable density of woody species was found in the seed bank, indicating a potential for pasture colonization. Soil compaction can not be considered a limitation to forest recovery in the study area. The removal of Brachiaria humidicola (Rendle) Schweick. and soil tillage can enhance the emergence of woody species seedlings in the seed bank.